In Vitro Susceptibility of Burkholderia pseudomallei Isolates to Cefiderocol and Ceftazidime/Avibactam from Odisha, India - Jena, Jayanti; Behera, Bijayini; Nayak, Gayatree; Mohanty, Srujana; Mahapatra, Ashoka; Purushotham, Prashanth; Radhakrishnan, Anjuna; Tripathy, Manaswiny (Journal of Laboratory Physicians, 2023)
Introduction and Objectives The availability of a limited arsenal of antibacterial agents effective against Burkholderia pseudomallei, the causative agent of melioidosis, together with sporadic reports of emergence of resistance necessitates an evaluation of in vitro activity of new antimicrobials against clinical B. pseudomallei isolates. Cefiderocol (CFDC), a novel siderophore cephalosporin, and ceftazidime-avibactam (CZA), a new β lactam combination agent, have shown promising results for the treatment of difficult-to-treat Gram-negative bacilli infections with limited treatment options. This study was conducted to determine the in vitro activity of CFDC and CZA against a contemporary collection of 60 B. pseudomallei clinical isolates.Materials and Methods Minimum inhibitory concentrations (MIC) of CFDC and CZA were determined by broth microdilution and E-test, respectively. The performance of disk diffusion was also evaluated for CFDC.Results All B. pseudomallei isolates were susceptible to CFDC and CZA with MIC range of 0.125 to 2 mg/L and 0.19 to 1 mg/L, respectively. Zone diameters for CFDC ranged from 31 to 40 mm.Conclusion CFDC and CZA exhibited excellent in vitro activity against 60 B. pseudomallei isolates. Further pharmacokinetic-pharmacodynamics studies and clinical trials are needed to prove the clinical efficacy of CFDC and CZA in the treatment of melioidosis.
Keywords: Burkholderia pseudomallei; Cefiderocol; Ceftazidime-avibactam